2023
DOI: 10.3390/jcm12062216
|View full text |Cite
|
Sign up to set email alerts
|

The Firmicutes/Bacteroidetes Ratio as a Risk Factor of Breast Cancer

Abstract: The gut microbiome can reflect the health condition of the entire body. Firmicutes and Bacteroidetes, the major phyla of the colon, can influence diseases related to obesity which are also risk factors for breast cancer. Therefore, the Firmicutes/Bacteroidetes (F/B) ratio was analyzed in patients with breast cancer. Bacterial extracellular vesicles were extracted from the serum of patients with breast cancer and healthy controls. Phyla Firmicutes and Bacteroidetes were analyzed using microbiome sequencing. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…The study was not without limitations, including the small sample size and the potential for confounding factors to influence the results. Additionally, changes in the F/B ratio have been associated with various conditions and dietary factors, such as enlarged prostate, non-alcoholic fatty liver disease (NAFLD), breast cancer, and food types, suggesting that our findings may not be specific to COVID-19 and T2D [34] , [35] , [36] , [37] . Therefore, future studies should be conducted with larger sample sizes, more comprehensive clinical data, and control groups to confirm these findings and explore the underlying mechanisms involved.…”
Section: Discussionmentioning
confidence: 84%
“…The study was not without limitations, including the small sample size and the potential for confounding factors to influence the results. Additionally, changes in the F/B ratio have been associated with various conditions and dietary factors, such as enlarged prostate, non-alcoholic fatty liver disease (NAFLD), breast cancer, and food types, suggesting that our findings may not be specific to COVID-19 and T2D [34] , [35] , [36] , [37] . Therefore, future studies should be conducted with larger sample sizes, more comprehensive clinical data, and control groups to confirm these findings and explore the underlying mechanisms involved.…”
Section: Discussionmentioning
confidence: 84%
“…Among the gut microbiota, Firmicutes and Bacteroidetes are two major bacteria, and the Firmicutes/Bacteroidetes ratio has a significant impact on maintaining gut homeostasis. An imbalanced ratio may lead to various diseases, such as inflammation, autoimmune diseases, and cancer 46 . In this study, the gut microbiota of NOD mice was highly enriched in Firmicutes , while the abundance of Bacteroidetes was decreased.…”
Section: Discussionmentioning
confidence: 55%
“…Bacteroidota, Deferri-bacterota, Proteobacteria, Actinobacteria, Firmicutes, and Desulfobacterota were the six center phyla of the gut microbiota, of which Bacteroidetes and Firmicutes accounted for over 95% of all ( Wang et al, 2022 ). The literature has demonstrated that Firmicutes/Bacteroidetes are positively related to intestinal health ( An et al, 2023 ). The present study shows that SJZD could markedly increase the Firmicutes/Bacteroidetes ratio compared to DSS, which implies that SJZD could regulate the transformation of enteric microorganisms into normal gut microbiota and promote gut health.…”
Section: Discussionmentioning
confidence: 99%